Innovative environment as a factor of the region’s competitiveness - A. A. Okutin (Путеводитель предпринимателя, 2020)
The article describes the approach to the essence of the innovative environment as an important factor in ensuring the competitiveness of the region and improve its socioeconomic development through the establishment of appropriate infrastructure; a comparison of the concepts of innovation environment, innovation system and institutional environment of innovative development; The factors influencing the formation of innovative environment of the region and classification of the factors influencing the formation of the innovation environment in the region.